2009
DOI: 10.1002/humu.21110
|View full text |Cite
|
Sign up to set email alerts
|

Update on mutations in glucokinase (GCK), which cause maturity-onset diabetes of the young, permanent neonatal diabetes, and hyperinsulinemic hypoglycemia

Abstract: Glucokinase is a key regulatory enzyme in the pancreatic beta-cell. It plays a crucial role in the regulation of insulin secretion and has been termed the glucose sensor in pancreatic beta-cells. Given its central role in the regulation of insulin release it is understandable that mutations in the gene encoding glucokinase (GCK) can cause both hyper- and hypoglycemia. Heterozygous inactivating mutations in GCK cause maturity-onset diabetes of the young (MODY) subtype glucokinase (GCK), characterized by mild fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
470
3
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 439 publications
(501 citation statements)
references
References 178 publications
17
470
3
11
Order By: Relevance
“…More than 600 different mutations have been identified throughout the 10 pancreatic b-cell exons of the GCK gene in .1,400 families (60). Almost all cases of GCK-MODY are due to missense (65%), nonsense, frameshift, or splice site mutations (61).…”
Section: Molecular Genetic Diagnosis Of Gck-modymentioning
confidence: 99%
“…More than 600 different mutations have been identified throughout the 10 pancreatic b-cell exons of the GCK gene in .1,400 families (60). Almost all cases of GCK-MODY are due to missense (65%), nonsense, frameshift, or splice site mutations (61).…”
Section: Molecular Genetic Diagnosis Of Gck-modymentioning
confidence: 99%
“…Impaired glucokinase activity was found in diabetic individuals [29,30]. Inactivation or the activation mutation of glucokinase gene have been linked to the development of maturity-onset diabetes of the young (MODY), Type 2 (MODY2) and persistent hyperinsulinemic hypoglycemia of infancy (PHHI) [31][32][33]. Patrick B et al have demonstrated that the activation of Akt signal pathway increases glucokinase gene expression [7].…”
Section: Figmentioning
confidence: 99%
“…There is considerable interest in the development of GKAs as potential therapies for type 2 diabetes because glucokinase activity plays an essential role in glucose-sensing by beta cells and glucose metabolism by hepatocytes [2][3][4][5]. The importance of this enzyme in glucose homeostasis was first widely recognised with the discovery of clinical syndromes resulting from loss-of-function and gain-of-function glucokinase gene mutations [6][7][8][9][10]. The gain-of-function mutations produce dominant/recessive clinical phenotypes of hyperinsulinaemic hypoglycaemia and are of particular pharmacological interest because they alter glucokinase function in a manner closely related to GKA action [11].…”
Section: Introductionmentioning
confidence: 99%